Physiological Analysis and Transcriptome Sequencing Reveal the Effects of Salt Stress on Banana (Musa acuminata cv. BD) Leaf - Wei, Junya; Liu, Debing; Liu, Yuewei; Wei, Shouxing (Frontiers in Plant Science, 2022)
The salinization of soil are widespread environmental problems. Banana (Musa acuminata L.) is a salt sensitive plant that growth, development, and production is constrained by salt stresses. However, the tolerance mechanism of this salt sensitive banana to salt stress is still unclear. The aim of this study was to investigate the influence of NaCl treatment on phenotypic, physiological and transcriptome changes in banana. We found that the content of root activity, MDA, Pro, soluble sugar, soluble protein and antioxidant enzymes activity in salt stress treatment were significantly higher than the control in banana. Transcriptome sequencing result identified overall 3378 DEGs in banana leaves and the KEGG analysis indicated that these DEGs were involved in phenylpropanoid biosynthesis process, ribosome process, starch and sucrose metabolism process, amino sugar process and plant hormone signal transduction process that had simultaneously changed expression under salt stress which indicated these DEGs maybe role to promoting BD banana growth under salt treatments. The genes which were enriched in phenylpropanoid biosynthesis process, starch and sucrose metabolism process and amino sugar process and plant hormone signal transduction process were specifically regulated to respond to the salt stress treatments response. Here totally 48 differentially expressed transcription factors (TFs) including WRKY, MYB, NAC and bHLH annotated under salt stress BD banana. In the phenylpropane biosynthesis pathway, all transcripts encoding key enzymes were found to be significantly up-regulated, indicating that the genes in these pathways may play significant function in the response of BD banana to salt stress response. In conclusion, this study provides new insights into the mechanism of banana tolerance to salt stress, which provides a potential application for the genetic improvement of banana salt tolerance.